The social issue in contemporary society : relations between companies, public administrations, and people - Stachowicz-Stanusch, Agata; Mercurio, Lorenzo; Stanusch, Natalia (Contemporary perspectives in corporate social performance and policy (Series), 2019)
It is widely observed that societies are changing, and new social issues are raising. The relationship between actors in the global environment and in the local as well, is changing because of financial crisis, new technological revolution, climate change, richness reallocation and concentration. We can see that value creation and management models in organizations are often uncoherent with the satisfaction of needs. The ability to create competitive advantages on a financial level seems to be increasingly developed. This can be sustained by the clear trend that leads companies to grow in size or create strong groups by shifting uncertainty over the weaker part of the market and unorganized systems and citizens. In this misalignment, empty spaces in the economic environment are opened. These spaces are those where the action of the public system can no longer be effective (or where it has never been) and where, more and more, the private interests are weak or absent. New wants are emerging in these areas and traditional models are no longer able to answer many of these needs.The book "The Social Issue in Contemporary Society: relations between Companies, Public Administrations and People" originates from a huge number of questions with the social issue as "fil rouge". In this perspective, the book is divided in four parts: "Introduction", "New Models and Tools for Public Administration", "New Models for New Companies" and "New Models for New Societies".A range of scholars that authored that book provide us with a different point of view about the problem that is underlined in the book title. We hope it will be a worthy inspiration for who dream a new idea of society.